Geotechnical investigation of pavement failure; causes and inherent solutions for sustainable highway construction in Sub-Saharan Africa (Rudarsko-geološko-naftni zbornik, 2020)
Engineering geological investigation of some unstable and stable sections of the Ibadan-Iwo-Osogbo highway was undertaken to unravel the intrinsic reasons responsible for continuous pavement failure along this road. Eighty disturbed and forty undisturbed soil samples were collected at different depths from twenty test pits of six selected failed sections (FS) and two stable sections (SS). Road construction analysis was done on these soil samples using standard methods. Liquid limit (22 - 64 % and 32 - 40 %), plasticity index (13 - 41 % and 12 - 18 %) and percentage fines (47 - 59 % and 32 - 41 %) indicated fair to poor and fair to good subgrade materials of FS and SS respectively. Medium to high plasticity and high clay content of soils of FS are indicative that the soils possess medium to high swelling potential. The activity of clay in soils of FS was approximately 0.3 – 1.2 and classified as inactive to normal clay. High linear shrinkage (>10 %), low compacted density and predominance of fines in soils of FS caused the instability. Exposure to excessive moisture led to strength reduction of the soils. Triaxial compression showed cohesion (72.6 - 127.0 kN/m2) and internal friction (12.7° -33.3°) indicating moderate to good shearing strength of the soils. A coefficient of compressibility of 0.1 – 0.5 kN/m2 indicated incompetency of the soils for road construction and the coefficient of consolidation was 0.01 – 0.30 m2/year. The subsoil of the FS is impervious with a relatively low coefficient of permeability, indicative high saturation in the region. Thus, the pavement failure was caused by water absorbing clayey soil, poor geotechnical parameters of the soils and a poor drainage network.